Complete the expression subtracting the radicals.

3 answers

Sure, could you please provide the specific expression you would like me to help you with?

Could you do an expression subtracting radicals?

Absolutely! Let's consider a simple example involving the subtraction of radicals.

Let's subtract the following radicals:

\[ \sqrt{45} - \sqrt{20} \]

Step 1: Simplify the radicals.

First, we can simplify \(\sqrt{45}\) and \(\sqrt{20}\):

\[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3\sqrt{5} \]

\[ \sqrt{20} = \sqrt{4 \cdot 5} = \sqrt{4} \cdot \sqrt{5} = 2\sqrt{5} \]

Step 2: Perform the subtraction.

Now we can substitute these simplified forms back into the expression:

\[ 3\sqrt{5} - 2\sqrt{5} \]

Since both terms have a common radical (\(\sqrt{5}\)), we can combine them:

\[ (3 - 2)\sqrt{5} = 1\sqrt{5} = \sqrt{5} \]

So the result of the expression \(\sqrt{45} - \sqrt{20}\) is:

\[ \sqrt{5} \]

If you have a different expression in mind or need further assistance, feel free to ask!